The Effectiveness and Influence of COVID-19 Vaccination on Perinatal Individuals and Their Newborns: An Updated Meta-Analysis - Zi-Jin Lei; Min-Xi Bai; Min-Jue Li; Peng Jin; Yu-Bin Ding (Canadian Journal of Infectious Diseases and Medical Microbiology, 2025)
Conclusion: Overall, COVID-19 vaccination during pregnancy effectively mitigates infection and adverse maternal/neonatal outcomes, supporting its clinical recommendation.